Journalism, Media & Communication Network : Final Report. - Breit, Rhonda; Romano, Angela; O'Donnell, Penny; McLellan, Trina (Office for Learning and Teaching, 2015)
This project sought to establish and develop a sustainable network of discipline scholars in the fields of journalism, media and communication (JoMeC). The key objectives of the network are: (i) To review and benchmark pedagogical elements of journalism, media and communication programs in Australia. (ii) To liaise with ALTC discipline scholars and develop an online learning and teaching hub for discipline scholars in journalism, media and communication to centralise relevant pedagogical, technological and organizational infrastructure and resources to support learning and teaching leadership and excellence in Australia. (iii) To develop systemic discipline standards for undergraduate and postgraduate courses in Australia that encompass journalism, media and communication, and thereby to sustain and improve learning and teaching. (iv)To enable JoMeC to advocate for learning and teaching: and to develop leadership capacity and offer expertise in addressing national higher education priorities.